Development Of Student Helpcare Application Model To Help Reduce Bullying Cases In Elementary Schools - Ahdhianto, Erif; Barus, Yohannes Kurniawan; Mudiono, Alif; Ardiansyah, Ahmad Nurrayhanwatsiq; Mahanani, Etyka Rina (Universitas Negeri Malang, 2024)
Bullying or harassment was a negative behavior involving the abuse of power or authority by individuals or groups with the aim of hurting others, which could lead to trauma. The aim of this research was to develop a reporting application called Student Helpcare to help reduce cases of bullying and harassment at the elementary school. This type of research was research and development (R&D) using the Borg and Gall development model, which consisted of ten stages including: information gathering and preliminary research; planning; initial product draft development; internal testing; revision; small-scale testing; revision; large-scale testing; final product revision; and dissemination. The instruments used were questionnaires, including product validation questionnaires given to media and language experts, practicality and effectiveness questionnaires given to teachers and students, and interview instruments given to the school principal, teachers, and students. The data collection stages in this research included questionnaires, interviews, and documentation as supporting evidence. The results of the study explained that the developed application product met valid, practical, and effective criteria. This application product received a validity score from media experts of 4.93, categorized as very valid, and from language experts, a score of 4.54, also categorized as very valid. The practicality score of the product from teachers received an average of 4.65, categorized as very practical, and the practicality score from students received an average of 94.2%, also categorized as very practical. The effectiveness of the product received an average score from teachers of 4.45, and from students an average score of 93.4%, indicating that the product developed was effective in reporting and receiving reports related to bullying or harassment in elementary schools.